Railway Lockouts in the Czech Republic and Possibility od their Optimization - Pluhař, Matěj; Šustr, Martin (Kaunas University of Technology, 2017)
The problem of railway lockouts are very extensive. From planning, through the proper process up to the economic and technological implications. This article describes the division, technology and specific examples of some railway lockouts on the railway lines in the Czech Republic.
Železniční výluky v České republice a možnosti jejich optimalizace
Keywords: railway lockouts; timetable; planning; výluka; jízdní řád; plánování